2015
DOI: 10.1016/j.envres.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Non-radiation risk factors for leukemia: A case-control study among chornobyl cleanup workers in Ukraine

Abstract: Background Occupational and environmental exposure to chemicals such as benzene has been linked to increased risk of leukemia. Cigarette smoking and alcohol consumption have also been found to affect leukemia risk. Previous analyses in a large cohort of Chornobyl clean-up workers in Ukraine found significant radiation-related increased risk for all leukemia types. We investigated the potential for additional effects of occupational and lifestyle factors on leukemia risk in this radiation-exposed cohort. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
8
1
2
Order By: Relevance
“…For example, a number of studies of farming populations now strongly suggest that pesticides and/or herbicides play a likely role in the etiology of CLL . However, in our study, occupational exposures to pesticides, solvents and benzene were not independent risk factors of CLL .…”
Section: Discussioncontrasting
confidence: 78%
“…For example, a number of studies of farming populations now strongly suggest that pesticides and/or herbicides play a likely role in the etiology of CLL . However, in our study, occupational exposures to pesticides, solvents and benzene were not independent risk factors of CLL .…”
Section: Discussioncontrasting
confidence: 78%
“…Previous analyses in the cohort of Chornobyl cleanup workers revealed significant radiation-related increased risk for all leukemia types, including chronic lymphocytic leukemia (CLL) [1][2][3]. Further study did not find additional effects of occupational and lifestyle factors on CLL risk in this radiationexposed cohort [4]. Numerous investigations emphasized the significance of genetic susceptibility to the development of tumors after exposure to carcinogens [5][6][7].…”
Section: The Distribution Of Tp53 Gene Polymorphisms In Chronic Lymphmentioning
confidence: 64%
“…After adjusting for radiation, there was found no clear association of leukemia risk with smoking or alcohol use but a two-fold elevated risk was identified for a non-CLL leukemia upon occupational exposure to petroleum (OR=2.28; 95% Confidence Interval 1.13,6.79). Risk was particularly high for the myeloid leukemia [19]. So, it can be suggested that exposure to similar confound factors has to be analyzed for MDS cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the frame of mentioned above epidemiological study "The Ukrainian-American study of leukemia and related disorders among Chоrnobyl cleanup workers" a set of data on a range of non-radiation exposures was collected [19]. Potential for additional effects of occupational (including exposure to petroleum) and lifestyle (cigarette smoking and alcohol consumption) factors on leukemia risk in this radiation-exposed cohort was investigated.…”
Section: Discussionmentioning
confidence: 99%